Neural Tissue Homeostasis and Repair Is Regulated via CS and DS Proteoglycan Motifs - Hayes, Anthony J.; Melrose, James (Frontiers in Cell and Developmental Biology, 2021)
Chondroitin sulphate (CS) is the most abundant and widely-distributed glycosaminoglycan (GAG) in the human body. As a component of proteoglycans (PGs) it has numerous roles in matrix stabilization and cellular regulation. In the central and peripheral nervous systems (CNS/PNS) CS has specific and important cell regulatory roles that control tissue function and homeostasis The CNS/PNS contains a diverse range of CS-PGs with important functional roles to play in directing the development of embryonic neural axonal networks, and the responses of cell populations in mature neural tissues to traumatic injury. Following brain trauma and spinal cord injury a stabilizing CS-PG-rich scar tissue is laid down at the defect site that prevents defect propagation to adjacent tissue regions. Neural tissues are some of the softest tissues in the human body and lack extensive collagenous and elastic supportive networks and this is important in the stabilization of such defects. Unfortunately, the CS concentrated in such gliotic scars also inhibits neural outgrowth and functional recovery. CS has well known inhibitory properties over neural behavior and various animal models of CNS/PNS injury have demonstrated that degradation of CS using chondroitinase improves neuronal functional recovery. Supportive collagenous or elastic networks are only present in the CNS/PNS in peripheral regions (meninges) or in specialized structures such as the motor neuron endplate in the neuromuscular junction or basal lamellar structures of the blood brain barrier. CS-PGs are present diffusely in the CNS but also form regions of denser extracellular matrix (ECM) termed perineuronal nets (PNNs) surrounding some neurons where they immobilize hyaluronic acid (HA) in hyalectan CS-PG aggregates with functionally significant roles to play in neural protection, synapse formation and neural plasticity. Despite the generally inhibitory neural cues delivered by CS-A and CS-C, some CS-PGs containing highly charged CS disaccharides (CS-D, CS-E) or related dermatan sulphate disaccharides can promote neural outgrowth and functional recovery. CS thus has varied cell regulatory properties and structural ECM supportive roles in the CNS/PNS depending on the CS glycoform present and its location in specific tissue niches and cellular contexts.